2004
DOI: 10.1063/1.1636524
|View full text |Cite
|
Sign up to set email alerts
|

All-organic thin-film transistors made of poly(3-butylthiophene) semiconducting and various polymeric insulating layers

Abstract: We have fabricated fully patterned all-organic thin-film transistors with a variety of organic polymer insulators. Poly(3-butylthiophene) deposited by spin coating was used as the active organic layer. We have built top-gate structures with gates printed on top of the gate dielectric layer. The field enhanced current is weak with poly(4-vinyl phenol), but much stronger with polyvinyl alcohol and cyanoethylpullulan. Carrier mobilities as large as 0.04 cm2/V s were measured in the case of cyanoethylpullulan. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…In contrast, Parashkov et al reported an opposite mobility trend when fabricating top-gate TFTs of poly(3-butylthiophene) (P3BT) as the semiconductor. [49] PEDOT:PSS source-drain contacts were defined on polyimide substrates on which a solution of the semiconductor was spin-coated. Subsequently, the gate dielectric was deposited by spin-coating and the device completed by screen-printing PEDOT:PSS gate lines.…”
Section: Reviewmentioning
confidence: 99%
“…In contrast, Parashkov et al reported an opposite mobility trend when fabricating top-gate TFTs of poly(3-butylthiophene) (P3BT) as the semiconductor. [49] PEDOT:PSS source-drain contacts were defined on polyimide substrates on which a solution of the semiconductor was spin-coated. Subsequently, the gate dielectric was deposited by spin-coating and the device completed by screen-printing PEDOT:PSS gate lines.…”
Section: Reviewmentioning
confidence: 99%
“…A promising solution is to reduce the subgap DOS at the channel through solution processed OSCs, and thus, very small gate dielectric capacitance can be used to realize low operation voltage [77], [112]. This approach provides the possibility of using a wide range of low-k polymer dielectric materials in a relatively thick layer to achieve stable low-voltage OTFTs [69], [74], [75], [88].…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…However, there are very few choices of suitable polymer dielectrics with high enough k values. Cyanoethylpullulan (CYEPL) [75], ferroelectric polymer poly (vinylidenefluoride-trifluoroethylene) [P(VDF-TrFE)] [76], and relaxor ferroelectric polymer poly(vinylidene fluoridetrifluoroethylene-chlorofloroethylene) [P(VDF-TrFE-CFE)] [77], [78] have been studied for lowvoltage OTFTs. P(VDF-TrFE-CFE) was reported to have a k value above 60 [78].…”
Section: Review Of Current Statusmentioning
confidence: 99%
“…The related build-up of negative charge close to the PVA/P3HT interface causes an accumulation of positive counter-charges in the semiconducting layer leading to an enhanced drain current. Such effects are frequently observed with highly polar gate dielectrics [6,[39][40][41][42] and have to be avoided by applying a different dielectric material or purification procedures. [43] Despite the unstable device characteristics, however, Figure 6 clearly reveals the potential of silver-copper nanoparticle based inkjet printed source, drain and gate electrodes to be applied in allliquid processed OFETs.…”
Section: Full Papermentioning
confidence: 99%